Techno-Economic Sensitivity Analysis of Integrated CCS–EOR for a 1,000 MW Ultra-Supercritical Coal-Fired Power Plant in Indonesia - Raden Ricko Satriyo; Renanto; Rendra Panca Anugraha; Roudlotus Salwa Aulia; Galuh Ferlianes Lestari (Eksergi, 2026)
Coal-fired power plants supply 60% of Indonesia's electricity and are major CO₂ sources. Integrating Carbon Capture and Storage with Enhanced Oil Recovery (CCS-EOR) offers a decarbonization pathway with economic benefits. This study evaluates techno-economic performance of an integrated CCS-EOR system for a 1,000 MW ultra-supercritical coal plant in Indonesia, simulated using Aspen HYSYS V14 automated with Python. A solvent blend of 35 wt% MDEA and 15 wt% PZ was used. Four parameters, minimum approach temperature (10–20°C), CO₂ removal efficiency (85–95%), absorber inlet gas velocity (2–2.5 m/s), and stripper Murphree efficiency (0.4–0.8) were varied across full factorial combinations, generating 162 scenarios. Four optimal scenarios were identified via multi-method optimization and assessed for economic feasibility at pipeline distances of 50–200 km. In the base case (90% removal), the system captured 5.66 million tons CO₂/year, with 28.91% energy penalty, Levelized Cost of CO₂ (LCoC) of -$64.53/ton, and Net Present Value (NPV) of $2.07 billion. CO₂ removal efficiency most influences LCoC, while ΔTmin most affects energy penalty. The Balanced Optimal scenario (LCoC -$65.65/ton, energy penalty 28.75%, NPV $2.20 billion) is recommended and remains viable up to 200 km.